The Perception of English by Polish and Lithuanian University Students: Implications for Higher Education - Małgorzata Karczewska; Vaida Žegunienė (In Gremium. Studies in History, Culture and Politics, 2019)
It cannot be denied that English has a special status in today's world, being used in international communication in both professional and private life. In order to have an insight into how the influence of English on other languages and its role in creating global awareness are indeed perceived, a study among Polish and Lithuanian university students was conducted. Answers to the questions included in the survey are presented in a comparative Polish – Lithuanian key in order to trace similarities and differences between the respondents in two European countries which joined the European Union in 2004 and has been fast developing since then.The study is a starting point in a discussion on practical implications for higher education stemming from the results of the research as it is believed that educational institutions are expected to respond to today’s world’s requirements and students’ expectations related to their future professional and private life.